DEVELOPING DIFFERENTIATED INSTRUCTION-BASED MATERIALS FOR TEACHING WRITING - Herya Darma Utami Ketut; Monik Rismadewi Ni Wayan (Journal on Studies in English Language Teaching (JOSELT), 2021)
The study aims at (i) developing writing material based on differentiated instruction in the eight year students of SMP Negeri 1 Singaraja, (ii) identifying whether the developed material is effective or not for the students’ writing competency. The data were collected by using rubrics and interview guides to find the compatibility of the existing materials and the developed materials with the syllabus and the criteria of suitable materials. Dick and Carey’s design model was employed as the present research procedures. The data which were obtained from the rubrics and checklists were quantitatively analysed by using the percentage of frequency. It was found that (i) the writing material was developed based on the criteria of a suitable material, a suitable writing material, and the combination of school-based syllabus and syllabus of BSNP for the eight-year students of Junior High School. The materials were finally developed based on three-level students, lower, average, and upper students. (ii) From the data of comparison between the result of pre-test and post-test, it was proved that the developed material could improve the students’ writing competency to achieve the standard competency stated in the syllabus.